Prevention EffortsImplementation of Diversion in Handling the Crime of Motorcycle Theft by Children at the Sorong Police - Nadila; muhamad hasan rumlus; Resdianto Willem (Equality Before The Law, 2026)
Theft offenses are frequently committed by juveniles, who are legally classified as children under Indonesian law. The involvement of children in theft is often associated with psychological immaturity and emotional instability, making them more susceptible to influence, persuasion, or coercion by adults to engage in criminal acts. This study aims to examine and analyze the implementation of diversion in the settlement of cases involving motorcycle theft committed by children. It adopts a juridical approach with a descriptive research design. The study employs both secondary data, collected through a literature review, and primary data, obtained through field research, particularly interviews conducted with investigators at the Sorong District Police. The findings reveal that the implementation of diversion in cases of motorcycle theft committed by children has been carried out in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The law requires investigators to initiate diversion during the investigation stage by involving all relevant parties, including the child offender, the victim, their respective parents or guardians, professional social workers, and the Correctional Center (Balai Masyarakat/Bapas), in a deliberative process aimed at reaching a Diversion Agreement. Several factors affect the effectiveness of diversion, including the limited number of law enforcement officers who have received specialized training on the Juvenile Criminal Justice System, victims' demands for excessive compensation motivated by financial gain, and the public's limited understanding of the objectives and procedures of diversion.